1988
DOI: 10.1021/bi00417a047
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal phosphoenolpyruvate-dependent phosphotransferase system: purification and characterization of the mannitol-specific enzyme IIImtl of Staphylococcus aureus and Staphylococcus carnosus and homology with the enzyme IImtl of Escherichia coli

Abstract: Enzyme IIImtl is part of the mannitol phosphotransferase system of Staphylococcus aureus and Staphylococcus carnosus and is phosphorylated by phosphoenolpyruvate in a reaction sequence requiring enzyme I (phosphoenolpyruvate-protein phosphotransferase) and the histidine-containing protein HPr. In this paper, we report the isolation of IIImtl from both S. aureus and S. carnosus and the characterization of the active center. After phosphorylation of IIImtl with [32P]PEP, enzyme I, and HPr, the phosphorylated pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 17 publications
(9 reference statements)
3
26
0
Order By: Relevance
“…A comparison of the crystal structures of E. coli EIIA Ntr and the EIIA Mtl domain shows that the fold of both proteins as well as the structure around the phosphorylation site, His-73 in EIIA Ntr and His-65 in EIIA Mtl (703), are nearly identical (73,905 (717). These findings are consistent with a regulatory role of EIIA Ntr through binding rather than through phosphoryl group transfer.…”
Section: The Pts Ntrsupporting
confidence: 55%
“…A comparison of the crystal structures of E. coli EIIA Ntr and the EIIA Mtl domain shows that the fold of both proteins as well as the structure around the phosphorylation site, His-73 in EIIA Ntr and His-65 in EIIA Mtl (703), are nearly identical (73,905 (717). These findings are consistent with a regulatory role of EIIA Ntr through binding rather than through phosphoryl group transfer.…”
Section: The Pts Ntrsupporting
confidence: 55%
“…We have recently demonstrated that mannitol transport in S. mutans has an EIIA component (Honeyman & Curtiss, 1992). This is similar to the mannitol PTSs found in other Gram-positive organisms (Fischer et al, 1989(Fischer et al, , 1991Reiche et al, 1988 ;Henstra et al, 1996).…”
Section: Introductionsupporting
confidence: 83%
“…However, the second possibility seems remote because the only genes in any other mannitol PTS system which are necessary for mannitol utilization are mtlA, mtlF and mtlD (Fischer & Hengstenberg, 1992 ;Fischer et al, 1991 ;Henstra et al, 1996Henstra et al, , 1999Lee & Saier, 1983 ;Reiche et al, 1988). These genes have not been interrupted in this case, and the observed effects are therefore probably due to the polar insertion of the interposon.…”
Section: Insertional Inactivation Of Mtlrmentioning
confidence: 86%
See 1 more Smart Citation
“…Expression of the various enzymes was induced by growth in the presence of the appropriate carbon source. Gluconate kinase, inositol dehydrogenase, and glucitol dehydrogenase activities were determined as described previously (16,30); mannitol PTS activity was determined according to the method of Reiche et al (32); mannitol-1-P dehydrogenase activity was measured according to the method of Novotny et al (31); glycerol kinase activity was measured according to the method of Deutscher and Sauerwald (11); oa-glucosidase activity was determined as described previously (4) by using p-nitrophenyl-ao-D-glucopyranoside as substrate, and ,B-galactosidase activity was measured according to the method of Miller (27) (Table 2). Repression of these enzymes by fructose was also no longer observed (9).…”
Section: Methodsmentioning
confidence: 99%